Wear-resistant corrosion-resistant super-hydrophobic fabric and preparation method thereof

Through the treatment of solutions such as citric acid, copper nitrate and sodium sulfide, wear-resistant and corrosion-resistant superhydrophobic fabrics are prepared, which solves the problems of complex preparation, high cost and vulnerability of materials in the prior art, and achieves efficient oil-water separation and long-term use super hydrophobic fabric.

CN119221278APending Publication Date: 2024-12-31HENAN UNIV OF URBAN CONSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510528.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing superhydrophobic materials are complex, costly, and have high environmental risks. The materials are susceptible to mechanical damage and chemical corrosion, resulting in loss of superhydrophobicity, making it difficult to achieve efficient oil-water separation that is resistant to wear and corrosion.

Method used

Using a combination of citric acid, copper nitrate and sodium sulfide solutions and low-surface energy substances, abrasion-resistant and corrosion-resistant superhydrophobic fabric is prepared through soaking and stirring, forming a micro-nano-level rough structure and hydrophobic component to improve the hydrophobicity of the fabric. Sex and lipophilic.

Benefits of technology

It realizes simple and economical superhydrophobic fabric preparation, with fast and efficient oil-water separation, self-cleaning, wear resistance and corrosion resistance, and is suitable for large-scale production and long-term recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005105328630000011
    Figure HDA0005105328630000011
  • Figure HDA0005105328630000012
    Figure HDA0005105328630000012
  • Figure HDA0005105328630000013
    Figure HDA0005105328630000013
Patent Text Reader

Abstract

The invention belongs to the technical field of super-hydrophobic fabrics. The invention provides a preparation method of a wear-resistant corrosion-resistant super-hydrophobic fabric. The method comprises the following steps: S1, immersing a fabric into a mixed solution of a citric acid solution and a copper nitrate solution, and stirring; s2, adding a sodium sulfide solution into the mixed solution with the fabric, and stirring; s3, continuously adding the solution containing the low-surface-energy substance and stirring; s4, taking out the fabric, washing and drying to obtain the wear-resistant and corrosion-resistant super-hydrophobic fabric. The preparation method is economical, environmentally friendly and easy to operate, the surface of the super-hydrophobic cotton fabric prepared through the preparation method has excellent hydrophobicity and lipophilicity, and rapid and efficient oil-water separation and cyclic separation can be achieved; and the coating also has good self-cleaning property, wear resistance and corrosion resistance, and can be recycled for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of super hydrophobic fabrics, and in particular relates to a wear-resistant and corrosion-resistant super hydrophobic fabric and a preparation method thereof. Background Art

[0002] Frequent oil spills and increasing industrial oily wastewater discharge have led to serious water pollution problems, which have seriously threatened the human living environment. Therefore, the development of new oil-water separation technology has become one of the problems that need to be solved urgently. Inspired by natural organisms, superhydrophobic surfaces made by biomimetic have provided a new idea for solving this problem. The superhydrophobic surface made by biomimetic has not only superhydrophobicity, but also superoleophilicity. If the superhydrophobic property is introduced into the surface of porous substrate materials, it can be endowed with superhydrophobic and superoleophilic properties. When the material comes into contact with an oil-water mixture, it can effectively adsorb the oil phase while repelling the water phase, thereby achieving oil-water separation by adsorption or filtration. This material has attracted widespread attention in the field of oil-water separation.

[0003] The performance of the surface of super-hydrophobic materials is mainly determined by their microstructure and chemical composition. The construction of super-hydrophobic surfaces usually requires the formation of micro-nano rough structures and the use of low surface energy materials for surface modification. To this end, researchers have proposed a variety of methods for preparing super-hydrophobic surfaces, including etching, hydrothermal, sol-gel, layer-by-layer self-assembly, electrodeposition, chemical vapor deposition, electrospinning technology, spraying technology, and solution immersion. However, these preparation methods often involve complex special equipment, expensive and toxic fluorine-containing reagents, long preparation cycles, and demanding environmental conditions. The widespread application of super-hydrophobic materials is greatly limited, and economic costs and environmental risks are increased in actual production. In addition, although researchers have developed a variety of super-hydrophobic porous materials for oil-water separation, the micro-nano rough structures of the prepared materials are often susceptible to mechanical damage or chemical corrosion in practical applications, resulting in the loss of surface super-hydrophobicity.

[0004] Therefore, there is an urgent need to develop a superhydrophobic cotton fabric that is easy to prepare, economical, environmentally friendly, wear-resistant and corrosion-resistant to meet the demand for efficient oil-water separation materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a super-hydrophobic fabric and a preparation method thereof. The preparation method is economical, environmentally friendly and simple to operate. The surface of the super-hydrophobic cotton fabric prepared by the preparation method of the present invention has excellent hydrophobicity and oleophilicity, can realize fast and efficient oil-water separation and circulation separation; it also has good self-cleaning property, wear resistance and corrosion resistance, and can be circulated for a long time.

[0006] The fabric prepared by the preparation method of the present invention not only has self-cleaning property, but also has excellent wear resistance and corrosion resistance, and can be recycled for a long time.

[0007] The technical solution adopted by the present invention to solve the above problems is as follows:

[0008] A method for preparing a wear-resistant and corrosion-resistant super-hydrophobic fabric comprises the following steps:

[0009] S1. Immerse the fabric in a mixture of citric acid solution and copper nitrate solution and stir;

[0010] S2. Add sodium sulfide solution to the mixture containing the fabric and stir;

[0011] S3. Continue to add the solution containing the low surface energy substance and stir;

[0012] S4. Take out the fabric, rinse and dry it to obtain a wear-resistant and corrosion-resistant super-hydrophobic fabric.

[0013] Further, the fabric is a natural fiber fabric, a synthetic fiber fabric or a blended fiber fabric, for example, cotton fabric, wool fabric, polyester fabric, acrylic fabric, polyurethane fabric, nylon fabric, cotton-polyester blended fabric, cotton-polyester fabric, etc.

[0014] Preferably, the fabric is a cotton fabric. The cotton fabric used has a very high porosity and a very strong adsorption, and the micro-nano structure and the hydrophobic component can be firmly coated on the fabric surface. Among numerous substrate materials, cotton fabric becomes an important choice for preparing super-hydrophobic materials with its environmental characteristics and high yield. Cotton fabric has excellent flexibility, air permeability, low cost, washability, regeneration and biodegradability, and shows a wide range of application potentials in industry and daily life. In addition, cotton fabric is rich in hydroxyl groups, has a higher porosity and good adsorption, and this provides favorable conditions for fixing micro-nano structure and hydrophobic components on its surface. Therefore, cotton fabric is considered to be one of the most potential substrate materials for preparing super-hydrophobic materials.

[0015] Furthermore, the fabric is washed and dried before the immersion.

[0016] Furthermore, the concentration of the citric acid solution is 0.1-0.2 mol / L.

[0017] Preferably, the concentration of the citric acid solution is 0.16 mol / L.

[0018] Furthermore, the concentration of the copper nitrate solution is 0.53-1.33 mol / L.

[0019] Preferably, the concentration of the copper nitrate solution is 0.89 mol / L.

[0020] Furthermore, the mixing volume ratio of the citric acid solution and the copper nitrate solution is (1:3) to (2:3).

[0021] Preferably, the mixing volume ratio of the citric acid solution to the copper nitrate solution is 1:2.

[0022] Furthermore, the concentration of the sodium sulfide solution is 1.17-2.91 mol / L.

[0023] Preferably, the concentration of the sodium sulfide solution is 1.92 mol / L.

[0024] Furthermore, in the solution containing the low surface energy substance, the concentration of the low surface energy substance is 0.02 to 0.08 mol / L.

[0025] Preferably, in the solution containing the low surface energy substance, the concentration of the low surface energy substance is 0.04 mol / L.

[0026] Furthermore, the low surface energy substance is at least one of dodecanethiol, stearic acid and lauric acid.

[0027] Furthermore, the solvent used in the solution containing the low surface energy substance is ethanol.

[0028] Preferably, the solution containing low surface energy substances is an ethanol solution containing dodecanethiol.

[0029] Furthermore, in the process of preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric, the added volume ratio of the mixed solution, the sodium sulfide solution and the solution containing the low surface energy substance is 4:1:4-6.

[0030] Furthermore, the stirring time is 10 to 50 minutes.

[0031] Furthermore, the rinsing is performed by sequentially rinsing with ethanol and deionized water.

[0032] The present invention also provides a wear-resistant and corrosion-resistant super-hydrophobic fabric prepared by the preparation method of the present invention.

[0033] The present invention has the following beneficial effects:

[0034] The present invention provides a method for preparing a wear-resistant and corrosion-resistant super-hydrophobic fabric, wherein the preparation method is simple and easy, has low cost, short preparation cycle, does not require special equipment and harsh conditions such as high temperature, does not involve toxic fluorine-containing substances, does not cause secondary pollution, and is suitable for large-scale production. The surface of the super-hydrophobic cotton fabric prepared by the preparation method of the present invention has excellent hydrophobicity and lipophilicity, can achieve fast and efficient oil-water separation and circulation separation; it also has good self-cleaning property, wear resistance and corrosion resistance, and can be recycled for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The SEM images of cotton fabrics at different magnifications after washing and drying.

[0036] Figure 2 SEM images of the super-hydrophobic cotton fabric provided in Example 1 of the present invention at different magnifications;

[0037] Figure 3 The surface state diagram and contact angle diagram of water droplets and rapeseed oil droplets dyed with methylene blue on cotton fabric after washing and drying;

[0038] Figure 4 The surface state diagram and contact angle diagram of the super-hydrophobic cotton fabric provided in Example 1 are water droplets and rapeseed oil droplets dyed with methylene blue;

[0039] Figure 5 A process diagram of a self-cleaning test of the super-hydrophobic cotton fabric provided in Example 1;

[0040] Figure 6 The surface state diagram and contact angle diagram of three corrosive droplets of 1M HCl, 1M NaOH and 1M NaCl on the super-hydrophobic cotton fabric provided in Example 1;

[0041] Figure 7 The contact angle data graph of the super hydrophobic cotton fabric provided in Example 1 after being immersed in three corrosive solutions of 1M HCl, 1M NaOH and 1M NaCl for 24 hours;

[0042] Figure 8 A graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Example 1 after 300 friction cycles;

[0043] Fig. 9 A comparison chart of the separation efficiency of the super-hydrophobic cotton fabric provided in Example 1 for different types of oil-water mixtures;

[0044] Fig.10 A graph showing the change in the cyclic separation efficiency of a mixture of dichloromethane and water by the super-hydrophobic cotton fabric provided in Example 1;

[0045] Fig.11This is a test diagram of the contact angle of the super-hydrophobic cotton fabric provided in Example 2 and Example 3 with deionized water. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The cotton fabrics used in the following examples and comparative examples were first washed and dried, specifically including: washing the cotton fabrics with ethanol and deionized water in sequence to remove pollutants on the surface of the cotton fabrics, and then drying them in an oven at 60° C. for later use.

[0048] Example 1

[0049] S1. Mix a citric acid solution (0.16 mol / L) and a copper nitrate solution (0.89 mol / L) in a volume ratio of 1:2 to obtain a mixed solution; immerse a cotton fabric in 20 mL of the mixed solution and stir for 20 min;

[0050] S2. Add 5 mL of sodium sulfide solution (1.92 mol / L) to the mixture containing the cotton fabric and stir for 20 min;

[0051] S3. Continue to add 20 mL of ethanol solution containing dodecanethiol (0.04 mol / L) and stir for 30 min;

[0052] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 60°C for 3 hours to dry it to obtain a wear-resistant and corrosion-resistant super-hydrophobic cotton fabric.

[0053] The super hydrophobic cotton fabric obtained in Example 1 was tested, and the results are shown in Figure 2 to Figure 10 .

[0054] Figure 1 The SEM images of cotton fabrics at different magnifications after washing and drying. Figure 1 It can be observed that the surface of untreated cotton fabric fibers is smooth without micro-nanoscale rough structures.

[0055] Figure 2 The SEM images of the super hydrophobic cotton fabric provided in Example 1 of the present invention at different magnifications. Figure 2 It can be seen that the surface of the cotton fiber becomes very rough, and a large number of micro-nano structures are evenly accumulated on the fiber surface to form a rough structure.

[0056] Figure 3 The surface state and contact angle diagram of water droplets and rapeseed oil droplets dyed with methylene blue on cotton fabric after washing and drying. Figure 3 It can be seen that both water droplets and oil droplets can completely wet the surface of the cotton fabric after washing and drying, and the contact angle is 0°.

[0057] Figure 4 The surface state diagram and contact angle diagram of the super-hydrophobic cotton fabric provided in Example 1 are water droplets and rapeseed oil droplets dyed with methylene blue. Figure 4 It can be seen that the oil droplets can infiltrate the surface of the super-hydrophobic cotton fabric provided in Example 1 with a contact angle of 0°, while the water droplets are spherical on the surface of the super-hydrophobic cotton fabric provided in Example 1 with a contact angle of 155±1°, which indicates that the super-hydrophobic cotton fabric provided in Example 1 has excellent super-hydrophobicity.

[0058] Figure 5 This is a process diagram of the self-cleaning test of the super-hydrophobic cotton fabric provided in Example 1. The self-cleaning test uses chalk powder as a pollutant to evaluate the self-cleaning ability of the cotton fabric. Figure 5 As shown, during the self-cleaning test, the cotton fabric was adhered to a glass slide with tape and the surface was covered with chalk powder. It was placed tilted in a culture dish, and then a syringe was used to provide a certain amount of water flow to clean the surface of the superhydrophobic cotton fabric in Example 1. It can be seen that the water can take away the chalk powder while rolling down. Finally, it can be observed that the surface of the cleaned cotton fabric is not wetted by water and is clean, which shows that the surface of the superhydrophobic cotton fabric prepared in Example 1 has excellent waterproof performance and good self-cleaning performance, which can prevent it from being contaminated.

[0059] Figure 6 The surface state diagram and contact angle diagram of the super hydrophobic cotton fabric provided in Example 1 are shown for three corrosive droplets of 1M HCl, 1M NaOH and 1M NaCl. Figure 6 It can be seen that the three types of droplets are all spherical on the surface of the super-hydrophobic cotton fabric provided in Example 1, and the contact angles are all higher than 150°.

[0060] Figure 7 The contact angle data of the super hydrophobic cotton fabric provided in Example 1 after being immersed in three corrosive solutions of 1M HCl, 1M NaOH and 1M NaCl for 24 hours. Figure 7It can be seen that after the super-hydrophobic cotton fabric provided in Example 1 was immersed in these three corrosive solutions for 24 hours, its surface water contact angle can still be maintained at more than 150 °. This is mainly due to the fact that when the super-hydrophobic cotton fabric provided in Example 1 is immersed in the corrosive solution, a large amount of air is trapped in the gap between the micro-nano rough structure, which can reduce the interaction between the corrosive liquid and the cotton fabric surface. In addition, the n-dodecyl mercaptan monolayer film self-assembled on the cotton fabric surface also plays an anti-corrosion role, further improving the corrosion resistance of the super-hydrophobic cotton fabric surface.

[0061] Figure 8 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Example 1 after 300 friction cycles. The friction cycle test method includes: laying the cotton fabric flat on 800-grit sandpaper, then placing a 100g weight on the cotton fabric, and pulling it in one direction for 10cm at a speed of 10cm / s, which is defined as one friction cycle. Figure 8 As shown, the super-hydrophobic cotton fabric of Example 1 still has super-hydrophobicity after 300 friction cycles, and the water contact angle is 153±1.2°.

[0062] Fig. 9 The following is a comparison chart of the separation efficiency of the super-hydrophobic cotton fabric provided in Example 1 for different types of oil-water mixtures. The specific method for detecting the separation efficiency includes: using a clamp to fix a piece of the super-hydrophobic cotton fabric provided in Example 1 between two glass tubes, and then pouring a mixture of 30mL of dichloromethane and 30mL of deionized water into the homemade separation device for oil-water separation test. Due to the super-lipophilicity of the prepared cotton fabric, dichloromethane quickly penetrates through the fabric under the action of gravity and is collected in a glass container placed under the separation device, while due to the super-hydrophobicity of the prepared cotton fabric, water is trapped in the upper glass tube. Similarly, several other types of oil-water mixtures (n-hexane, hexadecane, cyclohexane, rapeseed oil, chloroform) are separated and tested as above. Fig. 9 As shown, the separation efficiency of the super hydrophobic cotton fabric in Example 1 for these types of oil-water mixtures is higher than 98%.

[0063] Fig.10 The graph of the change of the cyclic separation efficiency of the super hydrophobic cotton fabric for the mixture of dichloromethane and water provided in Example 1. The specific method of the cyclic separation test includes: using a mixture of dichloromethane and deionized water to test the cyclic use ability of the cotton fabric prepared in this example, washing the cotton fabric contaminated by dichloromethane after separation with ethanol and deionized water in turn, drying at 60°C, and then performing the next cyclic separation. Fig.10 It can be seen that after 50 separations, the separation efficiency of the superhydrophobic cotton fabric in Example 1 for the mixture of dichloromethane and deionized water is still greater than 98%, which proves that the superhydrophobic cotton fabric in Example 1 has excellent oil-water separation ability and recyclability.

[0064] Example 2

[0065] S1. Mix a citric acid solution (0.1 mol / L) and a copper nitrate solution (0.53 mol / L) in a volume ratio of 1:3 to obtain a mixed solution; immerse a cotton fabric in 20 mL of the mixed solution and stir for 30 min;

[0066] S2. Add 5 mL of sodium sulfide solution (1.17 mol / L) to the mixture containing the cotton fabric and stir for 20 min;

[0067] S3. Continue to add 30 mL of ethanol solution containing dodecanethiol (0.02 mol / L) and stir for 30 min;

[0068] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 60°C for 3 hours to dry it to obtain a wear-resistant and corrosion-resistant super-hydrophobic cotton fabric.

[0069] The super hydrophobic cotton fabric prepared in Example 2 was tested. Fig.11 This is a test diagram of the contact angle between the super-hydrophobic cotton fabric and deionized water provided in Example 2. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 2 is 154.5±0.8°.

[0070] Example 3

[0071] S1. Mix a citric acid solution (0.2 mol / L) and a copper nitrate solution (1.33 mol / L) in a volume ratio of 2:3 to obtain a mixed solution; immerse a cotton fabric in 20 mL of the mixed solution and stir for 10 min;

[0072] S2. Add 5 mL of sodium sulfide solution (2.91 mol / L) to the mixture containing the cotton fabric and stir for 20 min;

[0073] S3. Continue to add 25 mL of ethanol solution containing dodecanethiol (0.08 mol / L) and stir for 30 min;

[0074] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 60°C for 3 hours to dry it to obtain a wear-resistant and corrosion-resistant super-hydrophobic cotton fabric.

[0075] The super hydrophobic cotton fabric prepared in Example 3 was tested. Fig.11 This is a test diagram of the contact angle between the super-hydrophobic cotton fabric and deionized water provided in Example 3. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 3 is 154±0.9°.

[0076] It can be seen from the test results of the above embodiments that the super-hydrophobic cotton fabric provided by the present invention has excellent hydrophobicity and oleophilicity, can achieve fast and efficient oil-water separation and circulation separation; it also has good self-cleaning properties, wear resistance and corrosion resistance, and can be recycled for a long time.

[0077] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0079] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a wear-resistant and corrosion-resistant super-hydrophobic fabric, characterized in that: The following steps are involved: S1. Immerse the fabric in a mixture of citric acid solution and copper nitrate solution and stir; S2. Add sodium sulfide solution to the mixture containing the fabric and stir; S3. Continue to add the solution containing the low surface energy substance and stir; S4. Take out the fabric, rinse and dry it to obtain a wear-resistant and corrosion-resistant super-hydrophobic fabric.

2. The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, wherein the fabric is a natural fiber fabric, a synthetic fiber fabric or a blended fiber fabric.

3. The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, wherein the concentration of the citric acid solution is 0.1-0.2 mol / L.

4. The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, wherein the concentration of the copper nitrate solution is 0.53-1.33 mol / L.

5. According to the method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, the mixing volume ratio of the citric acid solution to the copper nitrate solution is (1:3) to (2:3).

6. The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, wherein the concentration of the sodium sulfide solution is 1.17 to 2.91 mol / L. 7 . The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1 , wherein in the solution containing the low-surface-energy substance, the concentration of the low-surface-energy substance is 0.02 to 0.08 mol / L.

8. The method for preparing a wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, wherein the low surface energy substance is at least one of dodecanethiol, stearic acid, and lauric acid; and the solvent used in the solution containing the low surface energy substance is ethanol.

9. The method for preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric according to claim 1, characterized in that: In the process of preparing the wear-resistant and corrosion-resistant super-hydrophobic fabric, the added volume ratio of the mixed solution, the sodium sulfide solution and the solution containing the low surface energy substance is 4:1:4-6.

10. A wear-resistant and corrosion-resistant super-hydrophobic fabric, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.